Compressive Strength Assessment of Metakaolin Hollow Sandcrete Blocks - Ibrahim, M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
This study examines the effect of partially substituting metakaolin (MK) for cement on the hollow sandcrete block’s compressive strength. Sandcrete hollow blocks measuring 225 x 225 x 450 mm were made using a 1:6 mix ratio, which is one part cement to six parts fine aggregate (sand). The study was carried out by partially replacing metakaolin with cement at 0% to 35% at 5% intervals to assess the impact on the hollow sandcrete block’s strength. The blocks were cured using the sprinkling method, and compressive strength tests were conducted on the hollow sandcrete block samples at 1, 3, 7, 14, 21, and 28 days. The compressive strength of hollow sandcrete blocks samples ranges from 3.65 N/mm2 to 0.86 N/mm2. The compressive strength results showed that the optimum percentage of metakaolin (MK) replacement by weight of cement was 10% having a strength of 3.65 N/mm2 after 28 days of curing. These value meets the stipulated requirement specified by Nigeria Industrial Standard NIS 87 (2000), BS 6073, and National Building Code (2006) and are adequate for usage as non-bearing and load-bearing structures in areas where moisture infiltration may occur. The research was aimed at using metakaolin (MK) as a partial replacement of cement in the production hollow sandcrete blocks to curtail the reduction of cement components by block producers to produce low-quality sandcrete block for structural purposes and improve the strength properties of blocks in terms of its production.